Calpain-catalyzed cleavage and subcellular relocation of protein phosphotyrosine phosphatase 1B (PTP-1B) in human platelets. - Frangioni, J V (1993)
The non-transmembrane phosphotyrosine phosphatase 1B (PTP-1B) is an abundant enzyme, normally localized to the cytosolic face of the endoplasmic reticulum via a C-terminal targeting sequence. We have found that agonist-induced platelet activation results in proteolytic cleavage of PTP-1B at a site upstream from this targeting sequence, causing subcellular relocation of its catalytic domain from membranes to the cytosol. PTP-1B cleavage is catalyzed by the calcium-dependent neutral protease calpain and is a general feature of platelet agonist-induced aggregation. Moreover, PTP-1B cleavage correlates with the transition from reversible to irreversible platelet aggregation in platelet-rich plasma. Engagement of gpIIb-IIIa is necessary for inducing PTP-1B cleavage, suggesting that integrins regulate tyrosine phosphatases as well as tyrosine kinases. PTP-1B cleavage is accompanied by a 2-fold stimulation of its enzymatic activity, as measured by immune complex phosphatase assay, and correlates with discrete changes in the pattern of tyrosyl phosphorylation. Cleavage and subcellular relocation of PTP-1B represents a novel mechanism for altering tyrosyl phosphorylation that may have important physiological implications in cell types other than platelets.